Strengthening Women’s Entrepreneurial Capacity through Banana Chip Production in Kalongan Village, Semarang Regency - Sulaeman Fityan Saputra; Rama Dirga Dwi Sakti; Nasta Safira Ramadhina; Rohma Nur Anisa; Arneta Dyah Selina; Kharisma Jelita Putri; Chorinta Wulan Athaya; Abdul Malik; Jovan Daniel Pradana (Carmin: Journal of Community Service, 2026)
This community service program aimed to strengthen women's entrepreneurial capacity by developing banana chip production as a local economic product in Kalongan Village, Semarang Regency. It sought to empower women by improving practical skills in processing local agricultural resources into value-added products supporting household income and community-based entrepreneurship. The program used Participatory Action Research (PAR), involving 30 women selected through purposive sampling from the SEPATAH KATA community. Implementation proceeded through four stages: socialization of program objectives, training in banana chip production techniques, intensive mentoring during production, and evaluation of learning outcomes. A Likert-scale questionnaire assessed production accuracy, cooperation during production, and participants' independence and consistency. Data were analyzed descriptively using percentage analysis. Results showed positive impacts on participants' entrepreneurial skills and behavior: increased independence and consistency in production (45%), improved cooperation during production (30%), and better understanding of production procedures and step accuracy (25%). Participants also grasped the production stages and actively engaged in collaborative learning. These findings indicate that participatory training combined with continuous mentoring effectively enhanced participants' practical skills in transforming local resources into marketable products. The program successfully strengthened women's entrepreneurial capacity and supported the development of banana chip production as a sustainable local enterprise. Future follow-up efforts are recommended to focus on digital marketing assistance, product legality certification, improved packaging design, and sustainability monitoring of women's business groups.